Fluid biomarkers of white matter hyperintensities in cerebrovascular disease and neurodegeneration: a systematic review protocol. Issue 9 (14th September 2021) - Anastassiadis, Chloe; Vasilevskaya, Anna; Gumus, Melisa; Santos, Alexandra; Tartaglia, Maria Carmela
ABSTRACT: Objective: The goal of this systematic review is to evaluate the association between fluid biomarkers and white matter hyperintensities (WMH) in cerebrovascular disease and neurodegenerative disorders. While previous research has examined the etiology of WMH in specific diseases, we propose a comprehensive framework encompassing WMH of both vascular and non-vascular origin. Introduction: Although WMH have been mostly described in aging populations with cerebrovascular disease, extensive lesions also occur in non-vascular diseases. Such lesions are traditionally treated as a separate pathological entity from vascular ones, but recent work has challenged the appropriateness of that framework when probing WMH etiology. Comparing biomarkers associated with WMH across various pathologies may improve our understanding of their etiology. Inclusion criteria: The review will focus on cerebrovascular disease and neurodegenerative disorders and exclude infectious, metabolic, drug-induced, or radiation-induced white matter diseases. Original, peer-reviewed research on the relationship of WMH on magnetic resonance imaging with blood/cerebrospinal fluid biomarkers will be considered for inclusion. Postmortem studies will guide the selection of biomarkers of interest and the interpretation of our findings. Genomic markers will be excluded. Methods: The review will be conducted in accordance with PRISMA and JBI guidelines. English articles of interest published between 2000 and 2020 will be identified in MEDLINE and Embase. Two reviewers will perform abstract and full-text screening, standardized data extraction, and quality assessments of the selected studies. The relationship between each biomarker and WMH burden will be meta-analyzed, if possible, with subgroup or meta-regression analyses to assess differences between diseases. Systematic review registration number: PROSPERO CRD42020218298.